(untitled) (International Journal of Engineering and Computer Science, 2025)
Ensuring cost-effective logistics operations is a critical factor in sustaining competitiveness within Indonesia’s manufacturing and distribution industries. The textile chemical distribution sector is particularly challenged by escalating rental charges for third-party trucks, which have risen by approximately 15% annually, thereby creating long-term financial pressure and reducing control over operations. To address this concern, the company evaluated the feasibility of acquiring its own truck as an alternative. This study applies a descriptive-quantitative approach to compare leasing with truck ownership, employing Net Present Value (NPV), Payback Period (PP), Internal Rate of Return (IRR), and Modified Internal Rate of Return (MIRR) as evaluation indicators. Distribution demand from 2020 to 2027 was projected using seasonal decomposition, achieving a MAPE of 12.4%, which indicates reliable accuracy for cash flow forecasting. Although both options resulted in negative NPVs, truck ownership demonstrated more favorable outcomes. The investment’s payback period of 4.5 years remains within the truck’s eight-year economic life. Furthermore, the IRR of 16.21% surpasses the firm’s Minimum Attractive Rate of Return (MARR) of 15%, with a MIRR of 15.9% confirming feasibility. Overall, truck acquisition is more advantageous than leasing, offering financial efficiency, improved operational control, and strengthened supply chain resilience.